Vowel Perception and Transcription Trainer for Learners of English as a Foreign Language - Šimáčková, Šárka; Podlipský, Václav Jonáš (Research in Language, 2019)
We use the freely available program Praat to create a vowel-training application for learners of English familiar with IPA transcription. The application is easy to operate, allowing users to change the training difficulty, providing the listeners with immediate feedback, and adapting to their performance during a training session. To evaluate the effectiveness of the Trainer, performance of 59 Czech learners during a single training session and across multiple sessions was tracked. Results showed improvement both between sessions and within sessions. In the final training session, vowel identification accuracy showed considerable resistance to gradual addition of increasing levels of noise. Testing the trainer with additional 52 learners showed significantly higher error-rates for low-frequency words and supported the importance of top-down lexical effect in vowel identification.